2022
DOI: 10.3389/fpsyt.2022.814111
|View full text |Cite
|
Sign up to set email alerts
|

Models of Dynamic Belief Updating in Psychosis—A Review Across Different Computational Approaches

Abstract: To understand the dysfunctional mechanisms underlying maladaptive reasoning of psychosis, computational models of decision making have widely been applied over the past decade. Thereby, a particular focus has been on the degree to which beliefs are updated based on new evidence, expressed by the learning rate in computational models. Higher order beliefs about the stability of the environment can determine the attribution of meaningfulness to events that deviate from existing beliefs by interpreting these eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Similarly, when characterising belief updating on a trial-by-trial basis, Nassar and colleagues (2021) found that patients with schizophrenia show a generally reduced precision of beliefs and an inflexibility of belief updating. This finding allowed a simultaneous explanation of patients completely ignoring new information and persevering on previous responses (decreased likelihood precision), as well as the overly flexible behavioural adaptation to random noise (decreased prior precision; Katthagen et al, 2022). Thus, our findings directly align with this study, augmenting evidence that aberrant perception of task instability due to a decreased precision in both prior and likelihood information also extends along the continuum of psychosis into non-clinical populations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, when characterising belief updating on a trial-by-trial basis, Nassar and colleagues (2021) found that patients with schizophrenia show a generally reduced precision of beliefs and an inflexibility of belief updating. This finding allowed a simultaneous explanation of patients completely ignoring new information and persevering on previous responses (decreased likelihood precision), as well as the overly flexible behavioural adaptation to random noise (decreased prior precision; Katthagen et al, 2022). Thus, our findings directly align with this study, augmenting evidence that aberrant perception of task instability due to a decreased precision in both prior and likelihood information also extends along the continuum of psychosis into non-clinical populations.…”
Section: Discussionmentioning
confidence: 95%
“…Simultaneous aberrancies of heightened uncertainty in both likelihood and prior information may suggest that people with increasing psychotic-like experiences have general overestimation of uncertainty. In other words, they perceive greater instability or uncertainty in their inferred internal representation of the world (Katthagen et al, 2022; see Figure 7). The misallocation of precision may be hierarchical, such that imprecision in higher order prior beliefs may lead to a lack of regularisation that renders the environment seemingly volatile or unpredictable (Sterzer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be in line with previous research showing that autobiographical reflection is aversive for individuals with schizotypal traits 75 . A global deficit in updating prior beliefs based on new sensory data has been proposed as a common mechanism underlying the experience of psychosis at multiple levels of analysis 76 , 77 , including in CHR 78 . In schizophrenia, low positive self-beliefs are maintained in part by a lack of updating in response to belief-inconsistent information, e.g., positive feedback about the self 4 , 79 .…”
Section: Discussionmentioning
confidence: 99%
“…Future work could follow up on this to examine if overly certain, categorical perception in schizophrenia might lead to overly strong credit assignment to these percepts, thereby giving rise to delusions, particularly false beliefs about future outcomes. For a recent review of further literature on schizophrenia and adaptive learning, see Katthagen et al (2022).…”
Section: Schizophreniamentioning
confidence: 99%